(untitled) - Elison, George (Honolulu, 1981)
In this book, some of the leading American and Canadian scholars of Japan focus on a fascinating century. As the the sixteenth century began, Japan seemed to be breaking apart, with central authority powerless, and the populace tormented by incessant warfare among provincial barons.